Strengthening the global financial safety net: Moving relations between the IMF and regional financing arrangements forward - Pilar L'Hotellerie-Fallois; Axel Brueggemann; Matthieu Bussière; Livia Chiţu; Julia Estefanía; Sonsoles Gallego; Isabel Garrido; Caroline Janssens; Mary Keeney; Florian Lalanne; Alexander Landbeck; Christina Lerner; et al. (European Central Bank (ECB), 2018)
Since the global financial crisis, the Global Financial Safety Net (GFSN), traditionally consisting mainly of countries' own foreign exchange reserves with the International Monetary Fund (IMF) acting as a backstop, has expanded significantly with the continued accumulation of reserves, the sharp increase of swap lines between central banks, and the further development and creation of new Regional Financing Arrangements (RFAs). RFAs have expanded, reaching an aggregate size comparable to that of the IMF and becoming an integral layer of the safety net. Enhancing the cooperation between the IMF and RFAs so that they play complementary roles in case of global distress, becomes critical in order to further strengthen the multi-layered GFSN, while paying attention to issues such as moral hazard, stigma or exit strategies in connection with IMF-RFA cooperation. This paper presents recent experience and lessons learned in IMF-RFA cooperation and proposes how to improve their future interaction.
Keywords: F33; F34; F53; F55; 330; Global Financial Safety Net; Regional Financing Arrangements; International Monetary Fund; moral hazard; stigma; exit strategies